Surgical management of severe tricuspid regurgitation with portal hypertension and hypersplenism. Report of a case. - Irma Matos Santos; Francisco Bacallao San Julián; Luis Miguel Morales Pérez; Roberto Núnez Fernández; Yohana Díaz Landeiro; Guillermo Pérez Román (ECIMED, 2011)
The tricuspid regurgitation is a heart affection that frequently is associated to diseases of theleft side of the heart. It also obeys to different primary causes, among them, the infectiousendocarditis. Generally is well tolerated, the patient can arrive to cardiac surgery in an advancedstage of the illness, with portal vein hypertension, hepatic and splenic cronic congestion. We present the case of a patient -with severe tricuspid regurgitation, post infectious endocarditis,with severe portal vein hypertension and secondary hypersplenism, pancytopeniaand deficit of the clotting factors V and VII-; that was surgically intervened of a tricuspidvalve substitution with extracorporeal circulation without the induction of cardiac arrest.